Between democracy and putsch? – Censure motions in Romania (1989–2012). Issue 4 (December 2015) - Stan, Lavinia
Abstract: Though vilified as instances of "parliamentary putsch, " no-confidence censure motions remain significant constitutional tools through which the opposition can challenge the government in Romania, and publicly underscore its policy ineffectiveness in certain areas of activity. An overview of censure motions debated in the Romanian parliament from 1989 to 2012 reveals that center-left cabinets faced fewer challenges than their center-right counterparts, anti-communist forces were less skilled in articulating criticisms against cabinets, not all adopted motions led to cabinet removal, and motions became increasingly complex over time. Two motions adopted in 2009 and 2012, tabled by the center-left opposition against center-right cabinets, turned these parliamentary tools into powerful censure instruments.